The Effects of Cordyceps Mushroom Powder and Purified Mushroom Beta-Glucan on Nursery Pig Performance - J. Richert; M. Thayer; C. Chastain; A. Duttlinger; J. Feldpausch; R. Garcia; B. Richert; J. L. Nelssen (Kansas Agricultural Experiment Station Research Reports, 2019)
One hundred thirty-two gilts and barrows (18.2 d of age) weighing an average of 13.4 lb (Duroc × (York × Landrace)) were put on test for a 35-day growth trial to assess the effects ofCordycepsmushroom powder (MP) or purified mushroom beta-glucan (BG) as an antibiotic alternative in nursery diets. There were 6 diets, negative and positive controls (NC and PC), 150 and 300 ppm mushroom powder, and 150 and 300 ppm beta-glucan equivalents to the MP diets. Pigs were divided by weight, sex, litter, and assigned to 6 body weight (BW) blocks. Within BW blocks, sex ratios were constant in each pen. Pigs and feeders were weighed weekly to determine average daily gain (ADG), average daily feed intake (ADFI), and feed efficiency (F/G). During phase 1 (d 0 to 7), pigs fed the PC had increased ADG, ADFI, and d 7 BW (P<0.05) compared to pigs fed the NC. Beta-glucan and MP also increased ADFI in phase 1 (P<0.05) compared to the NC. During phase 2 (d 7 to 14), a health challenge (hemolyticEscherichia coli) went through half of the pigs with the other half challenged in phase 3 (d 14 to 21). This led to some erratic performance because of the pigs eating, but losing weight. In phase 4 there was a BG and MP interaction between source and dose. Pigs fed 300 level of MP had improved F/G, while those fed the 300 level of BG had poorer efficiency in phase 4 (P<0.07). Overall, there was an improvement (P>0.05) in F:G ratio in the PC when compared to the NC. There was also an interaction between source and dose for ADFI (P<0.05) between the BG and MP treatments. There was a significant improvement in F/G in MP and BG pigs compared to NC pigs (P<0.05). On day 35, there were no differences in final BW among treatments. A premarket weight was collected on all pigs at d 154 after weaning, and pigs fed the 300 BG from day 0 to 35 were 24.4 lb heavier than the NC (P<0.05) and 15.4 lb heavier than the PC (P<0.05).
Keywords: nursery pigs; growth; antibiotic alternatives